Pengaruh Struktur Modal Terhadap Perusahaan Manufaktur Yang Telah Go Public Di Bursa Efek Indonesia - Kurniawan, Hary; , Drs.Imronudin, M.M (2016)
This research was conducted in the Indonesia Stock Exchange in 2012 , which aims to influence capital structure , Long Term Debt to Asset ( LTD ) and Total Debt to Assets ( TDA ) on the performance of the company. The research method uses the entire population of manufacturing companies listed in Indonesia Stock Exchange , with a sample of manufacturing firms in 2012. The sampling technique is purposive sampling that the sample selected by using certain considerations tailored to the purpose of research or research problems developed . The analytical tool used : 1 ) Classical Assumption Test ( Normality Test , Test Multicolinearity , Test Heteroskidastity and Autocorrelation test ) , 2 ) Test Linear Regression , 3 ) Uji t , 4 ) F Test ( Test Accuracy Model ) and 5 ) Coefficient of Determination (R2) The results of data analysis can be obtained as follows : 1 ) lower variable t test shows LTD has a negative and significant impact on ROE . This is evidenced tcount > ttable ( -2.221 > -2.021 ) and Variable TDA has significant influence to ROE . This is evidenced tcount < ttable ( 2.473 > 2.021 ) . 2 ) based on test results obtained F Fcount > Ftable ( 3.375 > 3.23 ) , then Ho is rejected , Means jointly LTD variables and TDA together on ROE . So that the model used is fit. And 3 ) The results of data analysis ( R2 ) of 0.138 , meaning variation ROE changes can be explained by the variable LTD and TDA significant effect on ROE of 13.8 % . While the rest of 86.2 % is explained by other variables outside the model . Keywords : Long -term Debt to Assets ( LTD ) and Total Debt to Assets ( TDA ) on the performance of the company.